Analisis Pengembalian Kredit Terhadap Profitabilitas Pada PT Bank Sumut Cabang Gunungsitoli - Victorinus Laoli (Politeknik Ganesha Medan, 2019)
One manifestation of the important role of banking in a region, as implemented by PT Bank Sumut, Gunungsitoli Branch, is to distribute loans for investment, consumption and working capital for the people in the area. The purpose of providing credit for banks is the return of credit that earns interest and can increase income to finance activities and business continuity. From the results of research conducted with this data collection technique, it shows that PT Bank Sumut has a number of loans from 2009 to 2014 which each year rises. From this study, it is also known that the rate of credit repayment has a positive influence on the level of profitability.